Graus de coesão partidária no Brasil: os níveis de convergência programática das elites parlamentares subnacionais - Carlos Eduardo de Morais Freitas (2015)
This dissertation aims to present the degree of programmatic cohesion of six Brazilian political parties (PT, PSDB, PMDB, PDT, PSB and DEM), which is obtained by measuring the programmatic convergence levels of state lawmakers who composed these six parties in twelve legislative assemblies in 2008 and 2012. These data allow us to present a General Index of Cohesion (GIC) and relates the results to presidentialization of electoral disputes, the office or policy-seeking character of the party organization, ideology party, and affiliation time of state lawmakers. The proposal is to check to what extent these four factors combined are able to explain the degree of intra-party programmatic cohesion. The main source of quantitative data used results from surveys that are part of the first and second rounds of the "Trajectories, profiles and patterns of interaction of state lawmakers in twelve units of the federation", coordinated by the Legislative Studies Center of UFMG. Through such data was possible to measure the position of state lawmakers on three programmatic dimensions: state intervention in the economy, representation and political system, and human rights and civil rights. Furthermore, through the completion of the quantitative data with qualitative information from documental and theoretical sources, we propose the factors that help us to explain the index of cohesion. When considering total degrees of cohesion analyzed, it was revealed that the PMDB emerged as the most heterogeneous party, as expected in a consensual manner in literature; PT and PDT have far superior cohesion indices, showing that a significant portion of the Brazilian political elites in stratified parties share more than the interest of expanding its political space.